Narratives of recurrent flooding : the motives and definition of the situation according to urban poor communities of Malabon - MARIANO, TANYA L. (Archīum Ateneo, 2018)
Disaster risk reduction has historically followed a top-down, positivist, technocractic model that privileges "expert" knowledge and excludes the voices of risk-bearers, particularly those who are already marginalized. However, in order to craft meaningful interventions, the viewpoints of different stakeholders must be taken into account. The goal of this study is to uncover the meanings that urban poor communities living in flood-prone areas ascribe to recurrent flooding. The researcher conducted focus group discussions in Barangay Tinajeros and Barangay Potrero in Malabon, places that have a long history of flooding. Symbolic interactionism and dramatism form the theoretical framework of this study. The dramatistic pentad, which breaks narratives down into act, agent, scene, agency, and purpose, was used to analyze urban poor communities' accounts of their experiences with flooding. Several core meanings emerged: there is tension between their trust in their own agency and their recognition of the unpredictability of flooding; cause is attributed to geophysical and human factors; there are positive and negative effects; and recurrent flooding is an accepted part of life in Malabon. Implications on community identity, disaster risk reduction, and risk communication are outlined.